A low‐dose mindfulness intervention and recovery from work: Effects on psychological detachment, sleep quality, and sleep duration. Issue 3 (22nd March 2015) - Hülsheger, Ute R.; Feinholdt, Alina; Nübold, Annika; Michel, Alexandra; O'Shea, Deirdre; Hoppe, Annekatrin
<x xml:space="preserve">Abstract</x> Although playing a crucial role for the prevention of long‐term health impairment, interventions aiming at the improvement of employees' recovery processes are still scarce. In this study, we therefore investigated the effectiveness of a low‐dose mindfulness intervention for recovery from work. In addition, differential responding to the treatment in terms of treatment‐by‐baseline interactions was studied. A sample of 140 employees participated in a randomized field experiment with a self‐training and a wait‐list control group. Three central recovery processes (psychological detachment, sleep quality, and sleep duration) were assessed with event‐sampling methodology involving daily measurements over 10 workdays. Growth curve analyses revealed intervention effects on sleep quality and sleep duration. No effects were found for psychological detachment after work and for the proposed treatment‐by‐baseline interactions. Our findings are discussed in the context of occupational health promotion in general and mindfulness‐based interventions in specific. Practitioner points Although daily recovery from the demands of work has been shown to be vital for employee well‐being and performance, research on how workplace interventions can help improve recovery is still scarce. This study investigated the effectiveness of a brief, economic mindfulness intervention on processes that are vital for recovery – psychological detachment, sleep quality, and sleep duration. Findings revealed positive effects of the intervention on sleep quality and duration, but not on psychological detachment.